Factors explaining variation in the fecundity of female Baltic salmon (Salmo salar) - Tollerz Bratteby, Ulrika (2019)
Understanding factors influencing variation in fecundity is crucial to manage Atlantic salmon (Salmo salar) populations in the Baltic Sea. Larger individuals usually have a higher size-specific reproductive investment than smaller individuals, thus leading to a higher fecundity. Still, fecundity varies a lot among equally sized individuals and there is little known about what is causing this variation. In this study, I consider the effects of body length, condition and growth rate at sea on fecundity in Atlantic salmon females in the Baltic Sea. I collected fecundity data and data on growth rate history at sea in salmon originating from river Dalälven, which returned to spawn in mid-July to September 2004-2018, after spending two years at sea. I used scales to analyze marine growth patterns of the salmon. My results show that length is the factor that has the greatest influence on Atlantic salmon fecundity. Nevertheless, the relationship between fecundity, length and body condition varies among these years. In addition, there is a declining trend of how much of the variation in fecundity that can be explained by the interactive effect of length and body condition at the time of return to the river for spawning. Using circuli formation rate and inter-circuli distance as proxies for body growth, I show that growth rate during the first and second year at sea does not add to explain fecundity variation, after accounting for length and body condition. Still, being the factor determining body length, growth rate evidently has a great indirect effect on the fecundity of female Atlantic salmon. Individuals that grew poorly during their first year at sea did not compensate for their poor growth by growing faster during their second year at sea. In addition, the two growth estimates proved not to be related, which indicates that they are in fact independent factors of marine growth rate. Though it may be other factors than marine growth patterns that are causing variation in the fecundity of same-sized female Atlantic ...